Selective Electrochemical Conversion of CO2 into Methane on Ag‐Decorated Copper Microsphere - Rabin Dahal; Rohit Srivastava; Bishnu Prasad Bastakoti (ChemistryOpen)
Abstract We synthesized the silver‐decorated copper microsphere via the hydrothermal method followed by photoreduction of silver ions. Sub 100 nm Ag nanoparticles anchored on the surface of Cu microspheres enhance the electrochemical performance and the selectivity of the CO2 reduction into CH4. Incorporating Ag nanoparticles onto Cu lowers the charge transfer resistance, enhancing the catalyst's conductivity and active site and increasing the rate of CO2 reduction. The faradaic efficiency of silver nanoparticles decorated copper microsphere for methane was 70.94 %, almost twice that of a copper microsphere (44 %). The electrochemical performance showed higher catalytic properties, stability, and faradaic efficiency of silver‐decorated copper microspheres.